Legal analysis of creditor protection in bankruptcy without fiduciary guarantee registration - Septia Ningsih, Ratu; Shalsabila, Shalwa; Rahmalia, Astry; Alifah, Alifah; Maulana, Ayang Fristia (Journal of Law Science, 2025)
Fiduciary as a legal concept in Indonesia has undergone significant development, especially after the enactment of Law Number 42 of 1999 concerning Fiduciary Guarantees. With the expansion of the object of fiduciary guarantee, it now includes not only physical movable objects such as vehicles and equipment, but also intangible objects and immovable objects that cannot be encumbered with dependent rights. This shows that there is a legal adaptation that is responsive to the needs of transactions and economic development in the community. This research is a normative legal research using a legislative approach. Based on the results of the research, it can be concluded that a fiduciary guarantee deed that is not registered at the fiduciary registration office can result in a number of significant legal consequences. One of the main consequences is the loss of the power of execution of the guarantee, so that creditors cannot rely on the object of the guarantee as protection against their receivables.